1993
DOI: 10.1142/s0129183193000422
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulations of Surfactant Self Assembly

Abstract: In this letter we present the results of computer simulations of a simple water/surfactant model, from which we obtained a complete micellar size distribution. We are able to observe (equilibrium) dynamical processes such as the entering of single surfactants into micelles, single surfactants leaving micelles, the fusion of two micelles, and the slow breakdown of a micelle. We use our results to answer some controversial questions concerning the interactions that are essential for surfactant self-assembly.The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 1 publication
0
22
0
Order By: Relevance
“…Clearly these models allow for much flexibility in describing the molecular geometry and they can be studied by Molecular Dynamics. A generic off-lattice model has been utilized by Smit and co-workers [ 168] to elucidate micelle formation. Water and oil molecules are modeled by Lennard-Jones particles while the amphiphile is represented by a collection of particles bonded together via harmonic springs.…”
Section: Minimal Modelsmentioning
confidence: 99%
“…Clearly these models allow for much flexibility in describing the molecular geometry and they can be studied by Molecular Dynamics. A generic off-lattice model has been utilized by Smit and co-workers [ 168] to elucidate micelle formation. Water and oil molecules are modeled by Lennard-Jones particles while the amphiphile is represented by a collection of particles bonded together via harmonic springs.…”
Section: Minimal Modelsmentioning
confidence: 99%
“…By reducing the number of degrees of freedom together with the use of short range potentials, CGMD models can gain four to five orders of magnitude in speed compared with full-atom models, achieving length scales on the order of micrometers and timescales on the order of milliseconds. Encouraged by such computational efficiency, a number of CGMD models have been developed and used to study lipids and surfactants systems, including micelles [17,18], bilayers [19,20], micelle aggregation [21] and vesicle formation [22]. However, it should be noted that the computational efficiency of CGMD models is usually gained at the cost of loss in accuracy.…”
mentioning
confidence: 99%
“…There have been several simulation studies [113][114][115][116][117][118], including atomistic or coarse grained models, where micelle fusion and fission events were observed. For the fusion mechanism, more extensive reviews can be found in literature [77,119,120].…”
Section: Kinetic Process Involving Amphiphilic Moleculesmentioning
confidence: 99%